2014
DOI: 10.1055/s-0034-1371823
|View full text |Cite
|
Sign up to set email alerts
|

Hageman Factor C46T Promoter Gene Polymorphism in Patients with Hypercortisolism

Abstract: Glucocorticoids are a group of hormones with a particularly significant effect on hemostasis. In hypercortisolemic patients increased concentrations of II, VIII, and von Willebrand factors were reported. Considerably fewer studies were concerned with factor XII (FXII). There are reports of decreased FXII concentrations in both venous and arterial thrombosis patients. Also, it was determined that FXII C46T promoter gene polymorphism leads to changes of its concentration. The aim of the study was to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Alterations in gene expression levels frequently result from alterations in gene promoter activities ( 21 ). The RFLP results of the present study indicated that an increased number of GG SNPs in the GD group was identified in the −330 locus of the IL-2 promoter and the −1082 locus of the IL-10 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in gene expression levels frequently result from alterations in gene promoter activities ( 21 ). The RFLP results of the present study indicated that an increased number of GG SNPs in the GD group was identified in the −330 locus of the IL-2 promoter and the −1082 locus of the IL-10 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies considered that having the IL-2-330 GG and 114 TT genotype increases the risk of a variety of illnesses, including B-Cell Non-Hodgkin Lymphoma [27] and Gastric cancer [28,29]. Changes in gene promoter activity usually cause changes in gene expression levels, and the IL-2 gene that is clarified by its impact on cytokine [30]. Overall, the current data imply that genetic variants in the IL-6 and IL-2 genes are biologically relevant in the development of H. pylori-induced gastro-duodenal illness.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cortisol concentrations between 50 and 140 nmol/L in this test also had to have met at least one of the following criteria: abnormal serum circadian cortisol secretion, decreased morning ACTH concentration (£ 10 pg/mL), and/or increased 24-hour free cortisol urinary excretion. These diagnostic criteria were applied to our patients [23]. Moreover, in all SCS patients cortisol was not fully suppressed (> 50 nmol/L) in the two-day low-dose dexamethasone test (0.5 mg every 6 hours).…”
Section: Prace Oryginalnementioning
confidence: 99%